2014
DOI: 10.1002/2014ja020013
|View full text |Cite
|
Sign up to set email alerts
|

The responses of ionospheric topside diffusive fluxes to two geomagnetic storms in October 2002

Abstract: O + field-aligned ambipolar diffusive velocities V d and fluxes Ф d in the topside ionosphere have been calculated from the observed profiles of electron density, ion, and electron temperatures during a 30 day incoherent scatter radar experiment conducted at Millstone Hill (288.5°E, 42.6°N) from 4 October to 4 November 2002. Two geomagnetic storms took place during this period. During the negative phases (depleted electron densities) of these two storms, the magnitudes of the daytime upward V d and Ф d were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 40 publications
3
17
1
Order By: Relevance
“…In the topside ionosphere (Figure 8d), storm time vertical ion drifts were small and downward, whereas those during quiet time were large and upward. Similar storm time changes in vertical ion drifts were also seen by Chen et al [2014]. They reported that the daytime upward ambipolar diffusive velocity decreased during negative ionospheric storm effect periods over Millstone Hill.…”
Section: 1002/2015ja021832supporting
confidence: 65%
“…In the topside ionosphere (Figure 8d), storm time vertical ion drifts were small and downward, whereas those during quiet time were large and upward. Similar storm time changes in vertical ion drifts were also seen by Chen et al [2014]. They reported that the daytime upward ambipolar diffusive velocity decreased during negative ionospheric storm effect periods over Millstone Hill.…”
Section: 1002/2015ja021832supporting
confidence: 65%
“…The top boundary condition for the O + continuity equation is the O + diffusive flux. In this study, we used the method described in Chen et al (, ) to specify this flux by using Millstone Hill observed ionospheric parameters from 19 to 23 August. This flux was also modified such that the TIEGCM simulated electron density profiles could match the observed Ne profiles (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Figures and ). Note that O + diffusive flux in the topside ionosphere changes greatly with geophysical conditions, such as local time, solar and geomagnetic activity, and season and magnetic latitude (Chen et al, , , ). The default TIEGCM uses a simple topside O + diffusive flux that is a constant most of the time (upward during the day and downward at night), except that it varies with local time just near dawn and dusk and with magnetic latitude at low latitudes (Wang, ).…”
Section: Methodsmentioning
confidence: 99%
“…The transition time at dusk has remarkable importance for improving the upper boundary conditions of some theoretical models, such as the TIEGCM, because after this time the ion flux flows from the plasmasphere to the ionosphere. There are some common features can be found through comparing our statistical results at solar minimum with the storm case analysis at solar maximum of Chen et al (2014). During the autumn day, the increase of geomagnetic conditions decreases the magnitude of…”
Section: The Geomagnetic Activity Effectsmentioning
confidence: 53%